Mathematical model for vertical miller operation when snow mass transportation - D. S. Aleshkov; M. V. Sukovin (Вестник СибАДИ, 2022)
Introduction. An increase in the efficiency of snow removal work is due to an improvement in the characteristics of all components of this process, however, the creation of fundamentally new design schemes for snow blowers allows us to make qualitative changes in the problem of winter maintenance of roads, residential areas, etc. Materials and methods. A description of analytical studies of the dependence describing the design parameters of the feeder cutter for a rotary-milling snow blower is presented, on the basis of which the concept of a fundamentally new design of the feeder for a rotary-milling snow blower is formed. The description of the mathematical model of the presented design of the feeder is given.The structural scheme of the vertical cutter of the feeder of the rotary-milling snow blower is presented. Described are the main assumptions made in the compilation of the design scheme for the operation of the vertical cutter of the feeder of the rotary-milling snow blower. Equations have been obtained that describe the movement of a group of snow particles transported by a vertical mill and interact with each other in the process of movement, analytical dependences of the forces of normal reactions of the working elements of a vertical miller on its design and technological parameters. The initial conditions for the numerical solution of the presented equations of operation of the vertical milling cutter of the feeder of a rotary-milling snow blower are described.Results. The structural scheme of the vertical cutter of the feeder of the rotary-milling snow blower is described. Described are the main assumptions made in the compilation of the design scheme for the operation of the vertical cutter of the feeder of the rotary-milling snow blower. Equations are obtained that describe the movement of a group of snow particles transported by a vertical mill and interact with each other in the process of movement, analytical dependences of the forces of normal reactions of the working elements of a vertical mill on its design and technological parameters. The initial conditions necessary for the numerical solution of the presented equations of operation of the vertical milling cutter of the feeder of the milling-rotary snow blower are determined.Discussion and conclusion. The description of the mathematical model of the original design of the feeder of the throw-away snow blower is given. The necessity of a more complete substantiation of the initial conditions for the numerical solution of the equations of the work of the feeder of the throwing snow blower is indicated. This mathematical model makes it possible to proceed to a detailed study of the described cutter design in order to determine the working ranges of the design and technological parameters of the feeder with a vertical cutter.